2017
DOI: 10.1016/j.jaut.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Cells with Treg-specific FOXP3 demethylation but low CD25 are prevalent in autoimmunity

Abstract: Identification of alterations in the cellular composition of the human immune system is key to understanding the autoimmune process. Recently, a subset of FOXP3+ cells with low CD25 expression was found to be increased in peripheral blood from systemic lupus erythematosus (SLE) patients, although its functional significance remains controversial. Here we find in comparisons with healthy donors that the frequency of FOXP3+ cells within CD127lowCD25low CD4+ T cells (here defined as CD25lowFOXP3+ T cells) is incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
42
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 28 publications
11
42
0
6
Order By: Relevance
“…Supporting this tenet, reduced CD25 expression in aged Foxp3 + cells ( Figure 8D , X-axis, Figure 10A , X-axis) and their likely inability to regulate IL-2 is likely associated with their dysfunction and immunopathology during infection in aged mice ( 26 , 57 59 ). These data are also in accord with previous reports showing an association of CD25 low Foxp3 + cells with tissue autoimmunity ( 60 ). The contribution of IL-17A in the immunomodulatory role of T reg 17 cells is currently unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Supporting this tenet, reduced CD25 expression in aged Foxp3 + cells ( Figure 8D , X-axis, Figure 10A , X-axis) and their likely inability to regulate IL-2 is likely associated with their dysfunction and immunopathology during infection in aged mice ( 26 , 57 59 ). These data are also in accord with previous reports showing an association of CD25 low Foxp3 + cells with tissue autoimmunity ( 60 ). The contribution of IL-17A in the immunomodulatory role of T reg 17 cells is currently unclear.…”
Section: Discussionsupporting
confidence: 93%
“…T reg cell subpopulations within the mLN and colon tissue are analogous to those we have recently described in mouse 22 . We also identify an additional population, termed T reg -like cells, reminiscent of a CD25 − FOXP3 lo PD1 hi T reg population in the peripheral blood, although the latter was described to also express Ki67 34 . This population could represent uncommitted T reg cells experiencing transient loss of FOXP3 while retaining regulatory potential 23 or permanent loss of FOXP3 and adoption of a more pro-inflammatory phenotype after repeated stimulation 35 .…”
Section: Discussionmentioning
confidence: 94%
“…Multiple studies have set out to address the potential dysregulation of Tregs in patients with T1D by analyzing whether the frequency of Tregs is altered in peripheral blood. Although some have reported both increased (10, 11) and decreased (12) frequencies of Tregs, the majority of studies have concluded that no differences in peripheral blood Treg frequencies exist (1319). It is, however, noteworthy that several of these studies have used variable markers to define Tregs, and only some have used the most specific markers, CD25 in combination with CD127, FOXP3, and HELIOS (2023), to define peripheral blood Tregs.…”
Section: Introductionmentioning
confidence: 99%